Ko bolnik ne sodeluje ali ne more sodelovati - Pleterski-Rigler, Dušica (Zdravniški vestnik, 2001)
Background. Nowadays it is increasingly important for the physician to adequately inform the patient of his or her health situation, explain the options for treatment and obtain his or her consent. This principle is enshrined in the Oviedo Convention, a legal instrument with the power of law. Ethical questions aries when the patient is unwilling or unable to co-operate.Different problems are encountered with adult competent patients, in cases of limited mental capacity or with patients totally unable to consent. In children, the situation differs with age; adolescents opinion mustbe considered as increasingly important in decision making process, commensurate with their ability to understand and make rational choices. Specific ethical dilemmas arise with critically ill patients who refuse medical procedures or are unable to participate in medical decisions. Suicidalattempt cannot be taken to imply valid refusal of medical assistance. Conclusion. In exceptional situations when an appropriate informed consent cannot be obtained, the physician should take his decisions according to his best professional judgement and in the best interest of the patient.
Keywords: bolniki; Child advocacy; Ethics, medical; Informed consent; Insanity defense; medicinska etika; Mental competency; odločanje; Patient compliance